Conventional versus Modified Tarso-frontalis Suspension Surgery using Targeted Lid Crease for Simple Congenital Blepharoptosis with Poor Levator Action (Nepalese Journal of Ophthalmology, 2021)
Introduction: The routine technique of tarso-frontalis suspension surgery for simple congenital blepharoptosis with poor levator action is cosmetically less rewarding due to either an absence or asymmetry of the postoperative eyelid crease. The objective of this study was to assess the eyelid crease quality after a modified open method of tarso-frontalis suspension surgery compared to the closed method.Materials and methods: This was a retrospective comparative study reviewing the case sheets of all the patients undergoing unilateral tarso-frontalis suspension surgery with silicon rod employing Fox pentagon design from September 2017 to February 2019 at Mechi Eye Hospital, Jhapa, Nepal.  A review of 40 case sheets of congenital lid ptosis with poor levator function(